HIJAB DALAM PANDANGAN MUSLIMAH - Kartikaningrum, Ken Ayu (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2019)
This article discusses the hijab in the view of the Muslim community Caring for the Hijab Purwokerto. This research is a type of field research. In analyzing data, the instruments that researchers use are in-depth interviews, observations, and data that researchers get from journals, books, and newspapers. Researchers, in this case, use the Social Construction Theory from Peter L Berger's theory. This theory is more focused on the meaning and joint interpretation constructed in community networks. From the research conducted, the researchers focused on two main things, namely: (1) The view of the Muslim community caring for Hijab Purwokerto on the hijab. (2) Genealogy of Muslim Hijab Care for Hijab Purwokerto community understanding hijab